(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Resilience is the key to successful adaptation to change and the ability to resist new problems that makes a balance between vulnerability and the ability of individuals. This study aimed to review the ways of promoting resilience in treatment of vulnerable children and mothers.Method: To find related studies, search the main databases including PubMed, Web of Science (ISI), Scopus, PsycINFO, EMBASE, Google Scholar, and national databases such as Irandoc, Civilica, MagIran SID, using the key words of promoting, resilience and vulnerable children and mothers was performed from the beginning of database until August 2022.Results: In the initial search of databases, 1727 studies were obtained, of which 1532 studies were removed after duplication and 234 full-text studies were screened, of which 24 studies were included in the present study.Conclusion: There are different ways to improve the resilience of vulnerable people, which can be used to increase the resilience of these people against problems and improve their quality of life.